Development and Characterization of Ni55Ti45 Shape Memory Alloy for Biomedical Applications: Development and Characterization of Ni55Ti45 Shape Memory Alloy for Biomedical Applications - Amir, Aqsa; Atiq, Shabbar; Ahmad, Waheed; Saleem, Ayisha; Haseebah, Hafiza (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this study, a shape memory alloy of Ni55Ti45 was developed by Vacuum Arc melting technique under a vacuum of 10-5mbar. It was followed by homogenization in Nabertherm Tube furnace at a temperature of 1000°C for 54 hrs and subsequent furnace cooling. A series of tests had been performed in the laboratory in order to characterize the behavior of this alloy. Scanning electron microscopy results confirmed the presence of primary NiTi and secondary Ni3Ti phases respectively. X ray diffraction confirmed the BCC (body centered cubic) and HCP (hexagonal close packed) structures of NiTi and Ni3Ti respectively. In differential scanning calorimetry, no transformation was observed in the temperature range of 0ᵒC-1200ᵒC. This is indicative of the fact that the transformation temperature for shape memory effect lies below this temperature range.